Историческая интертекстуальность в романе П. Акройда «Дом Доктора Ди» - Рамазанов, А.М.; Бондаренко, Л.В. (Культура народов Причерноморья, 2014)
У статті розглядається актуальна щодо сучасного літературознавства проблема
співвідносин інтертекстуальності та історизму у постмодерністському романі відомого англійського
письменника Пітера Акройда “Дім Доктора Ді”. У дослідженні використовуються такі методи:
культурно-історичний, порівняльний, структурний та метод ретельного читання тексту.
Інтертекстуальність є основною характеристикою сучасного літературного тексту, у якому
знаходять відгуки багато інших текстів минулого. Під історичною інтертекстуальністю розуміємо
художню обробку історичних фактів та текстів у новому тексті, а також присутність у творі
історичних образів (доктор Ді). Роман має складну композіційну структуру – оповідання надається від
першої особи на двох часових рівнях, зображуючи історичні факти 16 віку та їх вплив на життя
головного героя у другій половині 20 століття. Отже історична інтертекстуальність є характерною
рисою творів П.Акройда, що робить його романи цікавими за змістом та формою. В статье рассматривается актуальная в современном литературоведении проблема
взаимоотношения исторических фактов и интертекстуальности постмодернистского текста в
романе известного английского писателя Питера Акройда «Дом доктора Ди». В исследовании
используются следующие методы: культурно-исторический, сравнительный, структурный и метод
внимательного прочтения. Под исторической интертекстуальностью понимаем художественную
обработку исторических фактов и предшествующих текстов в новом тексте, а также присутствие
исторических персонажей (доктор Ди). Роман имеет сложную сюжетную и композиционную
структуру. Повествование ведется от первого лица, однако, на двух временных уровнях – в эпоху
средневековья и в конце 20 века, изображая исторические события 16 века и их влияние на жизнь
главного героя, живущего в Лондоне четыреста лет спустя. Город, дом, главные герои являются связующими звеньями этих двух эпох и художественным проявлением исторической
интертекстуальности, что придает увлекательность романам П. Акройда. The article tackles the problem of historical intertextuality and its stylistic realization in modern
literature. Intertextuality is a major characteristic of any postmodern text, in which many other preceding texts
are incorporated. Peter Ackroyd’s novels are based on the intertextual play and generally perceived as
postmodern in their form and, to a certain extent, in content. They possess chfracteristics of various genres, such
as historical novel, Gothic novel, detective, fantasy, and others. “House of Doctor Di” is one of the most
acclaimed works of the author; it features historical events and figures of the middle ages and the second half of
the 20th century. The narration is presented from the first person on both layers – Doctor Di, a prominent
scholar in the 16th century and Mathew, a young scientist living in the second half of the 20th century. In both
epochs the events take place in London in the old house, which together with the town became a connection
between those times and the contemporary. The atmosphere of the “Dark Ages” is felt strongly in the novel,
which is full of mysteries, “red herrings” and gloom as well as with symbols and tokens. The Past and the
Present exist in the text independently as two temporary continuums parallel to each other. The house is
presented as somewhat closed territory, where characters are well-protected from the outer influence and only
the “selected” can be let in, but to get out appeared to be even more difficult than to get in. Historical
intertextuality also reveals itself in the language of the novel which differs greatly throughout the narration
reflecting the time the action takes place in.
Historical intertextuality in P. Akroyd’s works is a dual phenomenon and can be viewed as a content feature and
a stylistic device by means of which the author makes his novels exciting for the reader and attractive for
philologist.